Crosslinked porous polyimides: structure, properties and applications. Issue 45 (4th October 2021) - Narzary, Basiram Brahma; Baker, Benjamin C.; Yadav, Neha; D'Elia, Valerio; Faul, Charl F. J.
Abstract : Porous polyimides (pPIs) represent a fascinating class of porous organic polymers (POPs). Here the properties and functions of amorphous and crystalline pPIs are reviewed, and applications contributing to solutions to global challenges highlighted. Abstract : Porous polyimides (pPIs) represent a fascinating class of porous organic polymers (POPs). Not only do they exhibit high thermal and chemical stabilities, high surface areas, and energy storage capabilities, but their formation relies upon simple polycondensation reactions. A wide library of linker (dianhydrides) and core (amines) starting materials offers a vast range of crosslinked pPIs. This review details and carefully compares the unique properties and functions of both amorphous and crystalline pPIs. Furthermore, their applications in current global challenges in the fields of gas storage and separation, electrical energy storage, catalysis, drug delivery and sensors are reported. Finally, the review highlights the progress of pPIs since 2010 and offers an outlook and suggestions for future areas for exploration and potential applications within the field.